Traditional Ecological Knowledge and Inuit: Reflections on TEK Research and Ethics - Wenzel, George W. (ARCTIC, 1999)
The intimate knowledge that Inuit possess about the environment has figured prominently in North American Arctic research since at least the mid-1960s, when adherents of Julian Steward's adaptationist perspective essentially displaced the acculturation paradigm that until then had dominated Inuit studies. While Nelson's Hunters of the Northern Ice is the prototype of integrating traditional ecological knowledge (TEK) into the cultural analysis of Inuit, virtually all ecologically framed research on Inuit adaptation since has drawn extensively on TEK, if only as one of several information sources. Recently, however, Inuit and agencies and individuals concerned with the conduct of research in the North have expressed concern about the appropriation of this culturally specific knowledge. In the contemporary research environment of Nunavut, TEK is now a political (as well as scientific and cultural) concern. Most specifically, I conclude that 1) TEK is not qualitatively different from other scientific data sets; therefore, its analysis and interpretation must be subject to the same "rules" that apply to other forms of information; 2) TEK, because it is frequently contexturalized in individuals, demands closer ethical treatment than it has previously been accorded; and 3) the protection of TEK from "abuse" by scientists through intellectual property rights initiatives is problematic and unlikely to serve the long-term interests of either Inuit or researchers. La connaissance intime qu'ont les Inuit de l'environnement a tenu une place importante dans la recherche nord-américaine sur l'Arctique depuis au moins le milieu des années 1960, alors que les tenants de l'optique de l'adaptation prônée par Julian Steward supplantèrent essentiellement le paradigme de l'acculturation qui avait jusque-là dominé les études sur les Inuit. Alors que l'ouvrage de Nelson, Hunters of the Northern Ice, représente le prototype de l'intégration du savoir écologique traditionnel (SÉT) dans l'analyse culturelle des Inuit, pratiquement ...